Tectonic influences on late Holocene relative sea levels from the central-eastern Adriatic coast of Croatia - Shaw, Timothy Adam (2020)
Differential tectonic activity is a key factor responsible for variable relative sea-level (RSL) changes during the late Holocene in the Adriatic. Here, we compare reconstructions of RSL from the central-eastern Adriatic coast of Croatia with ICE-7G_NA (VM7) glacial-isostatic model RSL predictions to assess underlying driving mechanisms of RSL change during the past ∼ 2700 years. Local standardized published sea-level index points (n = 23) were combined with a new salt-marsh RSL reconstruction and tide-gauge measurements. We enumerated fossil foraminifera from a short salt-marsh sediment core constrained vertically by modern foraminiferal distributions, and temporally by radiometric analyses providing sub-century resolution within a Bayesian age-depth framework. We modelled changes in RSL using an Errors-In-Variables Integrated Gaussian Process (EIV-IGP) model with full consideration of the available uncertainty. Previously established index points show RSL rising from −1.48 m at 715 BCE to −1.05 m by 100 CE at 0.52 mm/yr (−0.82-1.87 mm/yr). Between 500 and 1000 CE RSL was −0.7 m below present rising to −0.25 m at 1700 CE. RSL rise decreased to a minimum rate of 0.13 mm/yr (−0.37-0.64 mm/yr) at ∼1450 CE. The salt-marsh reconstruction shows RSL rose ∼0.28 m since the early 18th century at an average rate of 0.95 mm/yr. Magnitudes and rates of RSL change during the twentieth century are concurrent with long-term tide-gauge measurements, with a rise of ∼1.1 mm/yr. Predictions of RSL from the ICE-7G_NA (VM7) glacial-isostatic model (−0.25 m at 715 BCE) are consistently higher than the reconstruction (−1.48 m at 715 BCE) during the Late Holocene suggesting a subsidence rate of 0.45 ± 0.6 mm/yr. The new salt-marsh reconstruction and regional index points coupled with glacial-isostatic and statistical models estimate the magnitude and rate of RSL change and subsidence caused by the Adriatic tectonic framework.